Lurbinectedin in patients with pretreated neuroendocrine tumours: Results from a phase II basket study. (September 2022) - Longo-Muñoz, Federico; Castellano, Daniel; Alexandre, Jerome; Chawla, Sant P.; Fernández, Cristian; Kahatt, Carmen; Alfaro, Vicente; Siguero, Mariano; Zeaiter, Ali; Moreno, Victor; Sanz-García, Enrique; Awada, Ahmad; et al.
Abstract: Background: Patients with neuroendocrine tumours (NETs) need alternative therapies after failure of first-line therapy. Patients and methods: This phase II trial evaluated lurbinectedin, a selective inhibitor of oncogenic transcription, at 3.2 mg/m 2 as a 1-h intravenous infusion every 3 weeks in 32 NETs patients treated in the second- or third-line setting. The primary efficacy endpoint was overall response rate (ORR) according to RECIST v1.1 assessed by the investigators. Secondary endpoints included duration of response (DoR), progression-free survival (PFS), overall survival (OS) and safety. Results: Two of 31 evaluable patients had confirmed partial responses (ORR = 6.5%; 95%CI, 0.8–21.4%). Median DoR was 4.7 months (95% CI, 4.0–5.4 months), median PFS was 1.4 months (95% CI, 1.2–3.0 months) and median OS was 7.4 months (95% CI, 3.4–16.2 months). Lurbinectedin showed an acceptable, predictable and manageable safety profile. The most common grade 3/4 toxicity was neutropenia (40.6%; grade 4, 12.4%; febrile neutropenia, 3.1%). Conclusions: Considering the exploratory aim of this trial that evaluated a heterogeneous population of NETs patients, and the signs of antitumour activity observed (two confirmed partial responses and seven long disease stabilisations), further development of lurbinectedin is warranted in a more selected NETs population. Trial registration number: Sponsor Study Code: PM1183-B-005-14. EudraCT number: 2014-003773-42. ClinicalTrials.gov reference: NCT02454972. Highlights: ORR with lurbinectedin in patients with NETs was 6.5% (95%CI, 0.8–21.4%). Median DoR, PFS and OS were 4.7, 1.4 and 7.4 months, respectively. Safety profile was predictable and manageable. Development of lurbinectedin in a selected NETs population is warranted.